Tides level indicator / Mohd Rahmani Mat Akhir, Muhammad Nashrullah Faisal and Muhammad Nazhiim Ikmal Hilmi - Mat Akhir, Mohd Rahmani; Faisal, Muhammad Nashrullah; Hilmi, Muhammad Nazhiim Ikmal (2015)
For a people who live nearby the sea or mostly depending on the sea like fisherman and people live near the coastline are having a hard time whenever the water tides change out of expectation. Usually by day light people indicate the water tides by observe near the seashore and from nearest jetty. But whenever day turn to night, there is no precise way on how to determine and indicate the situation. Then, there will be a problem when the tides level increase suddenly. This situation may give a big problem to the villagers and people nearby. Furthermore, loading process must be done by the normal tides level and how to measured this level without any devices. Nowadays, news also aware about this situation, the news shows the world how dangerous could be if this situation has no sequel and no action be taken. By creating ‘THE TIDES LEVEL INDICATOR’, this matter will solve in no time. The tides level indicator is one of its kind projects that exist with low cost required. For actual life product will cost a lot of expenses because the equipment is in Marine specification. The idea is simple, by combining two type of project which is water level indicator and a range finder. The indication process is due to the calculation frequency feedback proportional to time measurement. By that we can determine on what level of the water tides situation at the current time. This device that had been created was easily to handle. This device will indicate five situations that will show the user if the tides condition was high, low or the tide was at the normal situation. When the tides dangerously low or high this device will give an alarm and tell a user this condition. The user can take the earlier precaution. This device will indicate the situation at the difference place that this device were place on. The range of the situation based on the situation and condition of the place. This whole project will be using a board called Arduino Uno and ultrasonic sensor as its basics equipment. The calculation programming is done by Arduino board and using an ultrasonic module sensor as the device to detect the frequency of high peak. As additional, this project can be upgraded to multiple additional devices such as solar cell, GSM moderm, LCD display and act. Furthermore this device can place at the ship to indicate the deep of the sea.